1-[N-Methyl-N-(Phenyl)amino]-3- (4-Methylphenyl)Thiourea - Yeo, Chien Ing *; Tiekink, Edward R. T. * (MDPI, 2019)
The title compound, 1-[N-methyl-N-(phenyl)amino]-3-(4-methylphenyl)thiourea (1), was synthesized by the reaction of 1-methyl-1-phenyl hydrazine and 4-tolyl isothiocyanate, and was characterized by spectroscopy (1H and 13C{1H} NMR, IR, and UV), elemental analysis as well as by single crystal X-ray crystallography. In the solid state, the molecule exists as the thioamide tautomer and features an anti-disposition of the thioamide–N–H atoms; an intramolecular N–H· · · N hydrogen bond is noted. The molecular conformation resembles that of the letter L. In the molecular packing, thioamide-N1–H· · · S1(thione) hydrogen bonds lead to centrosymmetric eight-membered {· · · HNCS}2 synthons. The dimers are assembled into a supramolecular layer in the bc-plane by phenyl- and methyl-C–H· · · π(phenyl) interactions.